2020
DOI: 10.21037/apm.2020.02.13
|View full text |Cite
|
Sign up to set email alerts
|

Quietness Circ 0000962 promoted nerve cell inflammation through PIK3CA/Akt/NF-κB signaling by miR-302b-3p in spinal cord injury

Abstract: Background: In this study, we analyzed whether the neuroprotection of Circ 0000962 promoted neural inflammation in spinal cord injury (SCI) and its possible mechanism. Methods: Inflammation factors (TNF-α, IL-1β, IL-6 and IL-18) were measured using ELIS kit, and NF-κB, PI3K and phosphorylation-(p)-Akt protein expression were analyzed by Western blot analysis. Results: Circ 0000962 expression was decreased in SCI model rat and vitro model. Over-expression of Circ 0000962 decreased inflammation in vitro model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“… 27 Circ_0000962 was found to have a neuroprotective effect by activating PI3K/Akt and blocking of NF‐κB via miR‐302b‐3p to suppress inflammatory response in vitro cell model of SCI. 28 Additionally, Sun et al showed that circTYW1 contributed to functional recovery in rats after SCI and suppressed apoptosis in the lesion site as well as oxygen‐glucose deprivation (OGD)‐induced PC12 cells by activating ERK1/2 signaling through miR‐380/FGF9 axis. 29 Therefore, circRNAs are also have roles in function recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Circ_0000962 was found to have a neuroprotective effect by activating PI3K/Akt and blocking of NF‐κB via miR‐302b‐3p to suppress inflammatory response in vitro cell model of SCI. 28 Additionally, Sun et al showed that circTYW1 contributed to functional recovery in rats after SCI and suppressed apoptosis in the lesion site as well as oxygen‐glucose deprivation (OGD)‐induced PC12 cells by activating ERK1/2 signaling through miR‐380/FGF9 axis. 29 Therefore, circRNAs are also have roles in function recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GRB1 relieved SCI via altering miR-130b-5p/TLR4/NF-κB pathway [ 23 ]. circ_0000962 inhibited the inflammation in the SCI cell model via activating PI3K/Akt and inactivating NF-κB by sponging miR-302b-3p [ 7 ]. Thus, we explored the impact of LPS-induced XIST in the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al ( 2020 ) reported that the down-regulated Circ0001723 related to miR-380-3p-HIF-1α induces pro-inflammatory effects 1 day after experimental SCI in rats, via NF-κB signaling pathway suppression, including the expression of NLPR3 inflammasome and caspase-1 proteins. In vitro SCI studies in rats have shown that the upregulation of Circ0000962 decreased inflammation, via down-regulation of miR-302b-3p and subsequent modulation of PI3K/Akt and NF-κB signaling pathways (He et al, 2020 ). The high expression of circRNA-2960 was able to promote the secondary injury by sponging the miR-124, exacerbating the inflammatory response and inducing apoptosis (Chen et al, 2021 ).…”
Section: Circrnas In Sci Neuroinflammationmentioning
confidence: 99%